인삼 조사포닌의 조제 방법 개선 ( Improved Method for the Preparation of Crude Ginseng Saponin ) - 김시관; 곽이성; 김세원; 황석연; 고영수; 유종명 (Journal of ginseng research, 1998)
This stuffy was carried to establish a new efficient method for the preparation of edible crude ginseng saponin. The conventional butanol extraction and resin adsorption methods were compared for the contents of total crude ginseng saponin and major ginsenosides. Seventy- percent methanol extract was applied to Diaion HP-20 column and the resin was washed with Hn and eluted with absolute methanol. The methanol elute was dried in vivo and analyzed for its ginsenosides. Use of ethanol instead of methanol to make edible crude ginseng saponin gave a similar result. Butanol extraction was performed by the conventional method. The final aqueous layer from butanol extraction was passed through Diaion HP-20 column followed by elution with methanol and Diaion HP-20 passed fraction was extracted with butanol to recover remaining components, respectively, in order to determine saponin loss. TLC and HPLC qualitatively and quantitatively monitored Ginsenosides, respectively. Loss of ginsenosides was higher in butanol extraction method than in Diction HP-20 adsorption method. In addition, saponin fractions prepared by Diction HP-20 adsorption method showed higher content of each ginsenoside, showing 8.2% higher purity than that of butanol extracted fraction. From these results, we propose the resin adsorption method as a new efficient measure for the preparation of crude ginseng saponin, which is edible by using spirit instead of methanol.